MENGENAL PADEWASAN : KEYAKINAN, PILIHAN DAN HARAPAN - Ni Komang Ari Budiani; Anggy Paramitha Sari (Sanjiwani: Jurnal Filsafat, 2022)
Jyotisha as a science that focuses on the teachings of astronomy and astrology has an important role in the lives of Indonesian, especially Bali. Balinese people cannot be separated from this aspect, namely the election of auspicious days. ‘Time’ for the Balinese is interpreted as an expectation of the values ​​of goodness, luck. So, padewasan is applied in every procession, from the procession of preparation for birth to death. padewasan has a special place in the hearts of Balinese. There are; Tenung Mitra Satruning Dina, Tenung Jatu Karma and Tenung Pakeraban.